Optimization of chitinase production from bacillus cereus smg 1.1 using response surface methodology - Adnan Widodo; Indun Dewi Puspita; Ustadi Ustadi (Universitas Gadjah Mada, 2022)
Shrimp shell waste are potential to be processed further into value-added products, such as N-acetylglucosamine (GlcNAc). In the production of GlcNAc, biological approach is preferred and environmentally friendly to chemical treatment. Chitinase is an enzyme that plays a vital role in bioprocessing of shrimp shell waste into GlcNAc. Previously, Bacillus cereus SMG 1.1 was isolated from fermented shrimp paste (terasi) and showed the ability to produce chitinase. This study was designed to determine the optimum medium for the production of chitinase from B. cereus SMG 1.1 through the Response Surface Method (RSM) using a factorial design with 15 treatments. The optimization of the media was carried out by determining the factors that influence the production of chitinase through the Plackett-Burman design followed by optimization of the concentration of the media through the Box-Behnken design. The test was designed to assess the effect of the independent variables on chitinase activity. Placket Burman analysis shows that colloidal chitin, fructose, and MgSO4.5H2O were the significant components in the medium affecting the production of chitinase by B. cereus SMG 1.1. Box-Behnken analysis developed a linear model capable of predicting the response. The highest response value was achieved at a concentration of 0.75% fructose, 1.5% colloidal chitin, and 0.075% MgSO4.5H2O resulted in optimum chitinase activity of 0.0016 U/ml.